Quantification of medicine ball vertical impact forces: Estimating effective training loads - Ebben, W. P.; Blackard, D. O.; Jensen, R. L. (The Journal of Strength and Conditioning Research, 1999)
Quantification of training loads is necessary to determine an optimal range of training stimulus. While this is a simple matter when working with free weights and machines, it becomes more difficult with plyometric training, especially in the case of the upper body. Weight training is often performed at intensities approaching 100%. Plyometric training must be performed at an intensity high enough to cause adaptation in the relevant biomaterials but not at intensities so great as to prolong amortization and to compromise the use of the serial elastic component and stretch reflex. Research recommendations exist for lower-body plyometrics, such as the depth jump, that suggest an optimal range of jump heights. Nonetheless, recommendations often do not consider the subject`s body mass and impact force. Training loads for upper-body plyometrics performed with medicine balls have not been quantified. This study determines the vertical impact forces of the medicine ball (MB) for the purpose of quantifying training loads of MB drills with a vertical component. Based on results of the regression analysis, the following model was developed: vertical impact force = [(height {cm} × 5.58) + (mass {kg} × 59.65)] 468.30. The regression equation, expressed in pounds, is as follows: vertical impact force = [(height {in.} × 3.19) + (mass {lb.} × 6.09)] 105.37. The model is highly accurate, as evidenced by the high multiple R (R = 0.98) and low standard error of estimate (SEE) (37.4 N; 8.409 lb.). Recommendations are made to employ MB training loads of approximately 30% of 1 repetition maximum of biomechanically comparable weight-training exercise.